Design-driven innovation of bio-based circular materials. Design strategies and skills - Marinella Ferrara; Alessandro Squatrito (Agathón)
In recent years, design has turned its attention towards the Circular Economy where material issues are central. More and more companies and designers are turning their research towards ‘circular materials’ from the recycling of ‘technical materials’ or created from an organic base of processing/production or consumption waste and reintegrated into the biological cycle. The paper, focused on ‘bio-based circular materials’, presents the first phase of a research in progress, with the aim of mapping and systematising the strategies used for the conception, development, design, production and distribution of new materials and related products.